Pengembangan Kreativitas dan Produktivitas Siswa-Siswi Sekolah Dasar Islam Al-Azhar 8 Kembangan Jakarta Barat melalui Program Media Creative Class - Kamela Ezam Qiyami; Wati Nilamsari (Yumary: Jurnal Pengabdian kepada Masyarakat, 2021)
Purpose: This activity aimed to add, improve, and sharpen participant's skills, develop the creativity of elementary school children, and increase their productivity during the pandemic Method: Participatory Learning and Action (PLA) approach was utilized by assessing community involvement and interest in Creative Media Class's programs. Results: As a result of this activity, participants have gained new skills such as a better understanding of how they create creative content. Not only that, but they also know about ethics in social media. Making posters/flyers / Instagram post formats and video blogs are distributed through the official social media Media Creative Class, Instagram: @medikraf and their own. Conclusion: To develop student creativity for their skills, Media Creative Class helps them optimize technology for a solution to social distancing regulations.